2021
DOI: 10.3390/app11178110
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Transportation and Green Technology Innovation in Cities—From the View of the Industrial Collaborative Agglomeration

Abstract: This research uses a two-way fixed effect model to examine the correlation between the development of high-speed rail and the growth of green technology innovation by adopting the panel data of 284 Chinese cities between 2004 and 2013. The empirical results show that the supply of high-speed rail services has a significant promoting influence on the advance of urban green technology innovation capabilities. In particular, cities located in central and western China, along with those cities with relatively litt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Thus, the second hypothesis laid out earlier was also verified. Studies have shown that good transportation infrastructure is a necessary condition for the economic development of urban agglomerations, and simultaneously, the rational layout of the industrial structure will drive the development of urban agglomerations [79][80][81]. This is the same as the real situation in the Chengdu-Chongqing area.…”
Section: Discussion Of Empirical Resultsmentioning
confidence: 91%
“…Thus, the second hypothesis laid out earlier was also verified. Studies have shown that good transportation infrastructure is a necessary condition for the economic development of urban agglomerations, and simultaneously, the rational layout of the industrial structure will drive the development of urban agglomerations [79][80][81]. This is the same as the real situation in the Chengdu-Chongqing area.…”
Section: Discussion Of Empirical Resultsmentioning
confidence: 91%
“…Through the efficiency of cooperation, collaborative agglomerations can accelerate the flow of green innovation elements and promote the extension of the green innovation chain within and between regions. Knowledge-intensive enterprises and innovative industrial enterprises expand continuously, which helps to increase the frequency of green R&D cooperation within and across regions [23].…”
Section: Theoretical Analysismentioning
confidence: 99%
“…Labor market pooling and knowledge spillover exist in the tourism context (Kim et al, 2021). Benefiting from the agglomeration economy due to high urban centrality, the cost of labor force transfer and movement is greatly reduced, resulting in a more efficient allocation of labor (Lin et al, 2021a). Moreover, a large labor pool makes it much less expensive for tourism companies to search and find workforces, thus improving labor productivity.…”
Section: Mechanism Analysismentioning
confidence: 99%